A study on the fire safety system for timber longhouse / Eunice Harika Clarence - Clarence, Eunice Harika (UITM Sarawak,Kampus Samarahan, 2019)
The purpose of this study is to study about the fire safety system for the timber longhouses. It is to study the lack of fire safety awareness among the longhouse residents, the location of the longhouses in connection to the response time, the flammability of the structure's material, and the lack of safety features. The objective of this study is to identify the fire safety for the timber construction buildings,study the fire safety system practice for timber longhouse, and to evaluate the existing fire safety system of the timber longhouse. This study covers for longhouses made of timber throughout Sarawak. It has been found that there are two types of fire safety system, which is, active fire safety system and passive fire safety system. For the timber longhouse, there are not that many fire protection system that can be found.